2011
DOI: 10.1021/jp206153n
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Role of Anions on the Oxidative Decomposition Reaction of Propylene Carbonate

Abstract: The oxidative decomposition mechanism of the lithium battery electrolyte solvent propylene carbonate (PC) with and without PF(6)(-) and ClO(4)(-) anions has been investigated using the density functional theory at the B3LYP/6-311++G(d) level. Calculations were performed in the gas phase (dielectric constant ε = 1) and employing the polarized continuum model with a dielectric constant ε = 20.5 to implicitly account for solvent effects. It has been found that the presence of PF(6)(-) and ClO(4)(-) anions signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
214
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(232 citation statements)
references
References 31 publications
16
214
1
1
Order By: Relevance
“…For example, oxidation of carbonate solvents such as EC, PC, and DMC complexed with anions such as PF 6 − , BF 4 − , and ClO 4 − resulted in an anion nucleophilic attack on the solvent upon oxidation (electron removal) and deprotonation of the carbonates [34,35] that significantly reduced the oxidation stability of these solvent-anion complexes compared to values obtained for isolated solvents. Xing et al [36] reported that the oxidation potentials of EC 2 and EC 4 clusters were significantly lower than the intrinsic oxidation potential of an isolated EC and even lower than the oxidation potential of the EC-BF 4 − complex.…”
Section: Calculations Of the Electrolyte Oxidation Stabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…For example, oxidation of carbonate solvents such as EC, PC, and DMC complexed with anions such as PF 6 − , BF 4 − , and ClO 4 − resulted in an anion nucleophilic attack on the solvent upon oxidation (electron removal) and deprotonation of the carbonates [34,35] that significantly reduced the oxidation stability of these solvent-anion complexes compared to values obtained for isolated solvents. Xing et al [36] reported that the oxidation potentials of EC 2 and EC 4 clusters were significantly lower than the intrinsic oxidation potential of an isolated EC and even lower than the oxidation potential of the EC-BF 4 − complex.…”
Section: Calculations Of the Electrolyte Oxidation Stabilitymentioning
confidence: 97%
“…The majority of the studies considered isolated solvents or anions that do not explicitly interact with the electrode; in situations where there is no specific interaction such as hydrogen bonding with other electrolyte components; and where the solvent effect is included via the PCM. A few studies went beyond to include the condensed-phase interactions present in ionic liquids [32], cation-anion interactions [33], or solvent-anion interactions [16,[34][35][36][37]. The most successful were DFT predictions of shuttle redox potentials [26,38], which reported a close agreement with the experimental data showing a root mean square deviation of 0.08 V. Similarly, Wang, Buhrmester, and Dahn [38] reported excellent agreement between the calculated values for 17 redox shuttle additives, with a root mean square deviation between the calculated and measured oxidation potentials of 0.15 V and a maximum deviation of 0.25 V, indicating that DFT calculations at B3LYP/6-31G(d,p) could be effectively used for screening redox additives.…”
Section: Calculations Of the Electrolyte Oxidation Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the electrolyte is expected to be stable if the highest occupied molecular orbital (HOMO) of the electrolyte is lower than the cathode Fermi energy level. The density functional theory (DFT) computed electrochemical windows of the common electrolyte components [11][12][13][14][15] have been summarized in the past. 16 However, Fig.…”
Section: Solid Electrolyte Interphase (Sei) In Li-ion Batteriesmentioning
confidence: 99%
“…2e) to form volatile organic products. 65 This may expose reactive sites on the oxide surface, allowing other EC molecules to react and potentially deposit more protons. This will be considered in the future.…”
Section: 3940mentioning
confidence: 99%